Globalisation, lifelong learning and the learning society: sociological perspectives - Jarvis, Peter (Abingdon ; New York : Routledge, 2007)
Lifelong learning in the social context.
Human learning within a structural context.
Human learning within a global context.
Outcomes of the globalisation proces.
The information and the knowledge society.
The learning society.
Lifelong learning.
Life-wide learning.
Participants in lifelong learning: teachers and students.
The changing nature of research.
Policies, practices and functions.
The need for the learning society and lifelong learning.
Appendix: infinite dreams, infinite growth, infinite learning - the challenges of globalisation in a finite world.
Str. 217-238: Bibliografija.
Kazalo.
Keywords: cjeloživotno obrazovanje -- sociološki aspekti; učenje